(untitled) (Journal of actual problems of jurisprudence, 2019)
Any of the parties of process has the right to show an initiative – to begin collective negotiations. Representatives of the party initiator send to representatives of other party the written offer in any form of the beginning of collective negotiations. The party which has received the offer, is obliged to enter negotiations within seven calendar days. Keywords: collektivte agreement, parties, contrakt